MAJLIS TAKLIM DAN AKTUALISASI VISI ISLAM TRANSFORMATIF - Firman Nugraha (FASTABIQ: JURNAL STUDI ISLAM, 2020)
The purpose of this article is to describe the actualization of the transformative Islamic vision within religious economic movement. The transformative vision is the theological spirit embodied in the Qoran. A spirit that manifests to da'wah movement. Da'wah actions that answer problems of Ummah rather than just verbal activities. Da'wah action can be started from the activities held in  majelis taklim. Majelis taklim transforms a laboratory for social change in Muslim circles. The existence of majlis taklim is extraordinarily transformed into social capital as transformative vision formulation through reading the context of Muslims challenges, while referring to the Qur'anic doctrine. Throughout the theology of change, da'i has become not only a religious social elite, but also a person who has vision of change in society by a means of da'wah movement.Keywords: da'wah, social change, transformative theology